OC-026 PERFORMING A SLIT ON THE MESH TO ENCIRCLE THE CORD STRUCTURES DURING LAPAROSCOPIC INGUINAL HERNIA REPAIR - A SYSTEMATIC REVIEW AND META-ANALYSIS. (13th October 2022) - Demetriou, G; Ahmad, M S; Robinson, S J
Abstract: Aim: There are several modifications in the technique for the placement of mesh during laparoscopic inguinal hernia repair. The present study aimed to provide stronger evidence in establishing whether the slit mesh technique is superior to the non-slit technique (the most common practice). The primary outcome was recurrence and secondary outcomes were postoperative groin pain, bleeding, seroma formation and duration of surgery. Material & Methods: Eligible studies had to compare the two methods of mesh placement slit Vs non slit in laparoscopic TEP or TAPP inguinal hernia repair. Databases searched were Embase, Medline, Cochrane collaboration, NICE guidelines search. The meta-analysis was conducted using Review Manager software 5:4. The outcomes were expressed in odd ratios with their 95% confidence intervals. Where significant heterogeneity existed (I 2 >75%) a random effects model was used otherwise a fixed effects model was used. Results: Five studies included, all were single centre studies, 4 retrospective and one prospective observational studies. 1076 patients included, 633 in the slit group and 434 in the non-slit group. The male to female ration was 9:1. There were 10 (1.5%) recurrences in the slit group compared to 12 (2.5%) in the non-slit group 0.62, 95% CI (0.27–1.41). There was no difference in the incidence of post-operative bleeding (1.21, 95%CI 0.4–3.66), seroma formation (1.5, 95% CI 0.81–2.76), or post-operative neuralgia (0.98, 95%CI 0.11–8.92). Conclusion: There is no advantage in performing a slit on the mesh to encircle the cord structures during laparoscopic inguinal hernia repair.